2015
DOI: 10.1111/risa.12481
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Reach of Participatory Risk Management: Testing an Online Decision‐Aiding Framework for Informing Internally Consistent Choices

Abstract: This article presents research aimed at developing and testing an online, multistakeholder decision-aiding framework for informing multiattribute risk management choices associated with energy development and climate change. The framework was designed to provide necessary background information and facilitate internally consistent choices, or choices that are in line with users' prioritized objectives. In order to test different components of the decision-aiding framework, a six-part, 2 × 2 × 2 factorial exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…We draw on the literature concerning the development and testing of decision support frameworks in order to elicit public preferences regarding the energy system (change) (Bessette et al, 2014;Bessette et al, 2016;Demski et al, 2017;Mayer et al, 2014;Pidgeon et al, 2014). In contrast to the approach applied in the acceptance literature, here the respondents are asked to generate their preferred portfolios based on a set of different energy technologies or conservation measures.…”
Section: Acceptance Vs Portfolio Choicementioning
confidence: 99%
“…We draw on the literature concerning the development and testing of decision support frameworks in order to elicit public preferences regarding the energy system (change) (Bessette et al, 2014;Bessette et al, 2016;Demski et al, 2017;Mayer et al, 2014;Pidgeon et al, 2014). In contrast to the approach applied in the acceptance literature, here the respondents are asked to generate their preferred portfolios based on a set of different energy technologies or conservation measures.…”
Section: Acceptance Vs Portfolio Choicementioning
confidence: 99%
“…This open approach and the abstract ranking have been previously used in decision science research regarding energy policy and showed internally consistent choices (Bessette, Campbell-Arvai, and Arvai 2015).…”
Section: Discussionmentioning
confidence: 99%
“…From a practical standpoint, our research findings can be utilized to facilitate more effective communications dealing with various risk issues, not necessarily confined to controversies associated with HVPL installations. For instance, the key element for successful risk management strategy, especially in the context of a multistakeholder decision‐aiding framework, is to design a collaborative decision‐making environment where individual stakeholders can actively participate in all decision‐making stages with a high degree of deliberation, which, in essence, requires effective communications among the stakeholders as they share pertinent information supporting their respective decisions . How can we effectively share this decision‐support information with all involved stakeholders?…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For instance, the key element for successful risk management strategy, especially in the context of a multistakeholder decision-aiding framework, is to design a collaborative decision-making environment where individual stakeholders can actively participate in all decisionmaking stages with a high degree of deliberation, which, in essence, requires effective communications among the stakeholders as they share pertinent information supporting their respective decisions. (51) How can we effectively share this decision-support information with all involved stakeholders? An important aspect to consider in responding to this question is that individuals, more often than not, process the given information filtered through their cognitive heuristics in the course of reasoning, and culturally shared norms regarding the preferred nature of social relations, as this research suggests, constitute an important dimension of their cognitive heuristics, which are often long-lasting and resistant to short-term drastic change.…”
Section: Conclusion and Discussionmentioning
confidence: 99%